Institutional and technological innovations to foster agro-industrialization in Uganda: Insights from the dairy value chain - Van Campenhout, Bjorn; Nabwire, Leocardia; Minten, Bart; Ariong, Richard M. (International Food Policy Research Institute, 2020)
This policy note summarizes findings from a dairy value chain study in Uganda that documented the institutional and technological innovations associated with the transformation of the sub-sector from a USD 2 million industry in 2008 to a USD 150 million industry in 2017. Uganda is now one of the largest exporters of dairy products in Africa. Using primary data obtained from dairy farmers, traders, and processors, we examine the drivers of this transformation of Uganda’s dairy sub-sector. The insights gained can guide policy and investment decisions for upgrading other agricultural value chains that have been prioritized for agro-industrialization in the medium- and long-term national development plans of Uganda.